BindingDB Entry 50001505: Discorhabdin alkaloids from Antarctic Latrunculia spp. sponges as a new class of cholinesterase inhibitors. - BindingDB (BindingDB, 2020)
Small molecule binding data for protein Acetylcholinesterase, Cholinesterase, and Cholinesterases; ACHE & BCHE, Uniprot O42275, P22303, and P81908